Investigation of the Influence of Plate Thickness on Orifice Flow Using the Computational Fluid Dynamics Method - Mokhammad Bahtiar Rivai; James Julian; Fitri Wahyuni; Riki Hendra Purba (Universitas Muhammadiyah Metro, 2025)
Piping systems provide effective fluid distribution and are crucial to industrial operations. Despite their effectiveness, flow control devices like orifice plates can result in significant pressure drop that can lower system efficiency and wear out the systemâ€™s mechanical components. This study aims to optimize orifice plate design by examining the effect of plate thickness on flow characteristics using Computational Fluid Dynamics (CFD). Simulations were conducted on orifice plates with thicknesses ranging from 1.5T to 3.0T under Reynolds numbers from 10â´ to 10â¶. Results show that increasing the thickness reduces pressure loss, with the 3T configuration achieving a 1.35% reduction compared to the baseline. Improvements are linked to a higher discharge coefficient (Cd), shorter flow reattachment distance (Xr), smaller recirculation zones, and reduced velocity through the orifice throat. These findings suggest that geometric modifications can enhance flow performance and reduce the risk of mechanical damage in piping systems.